Body mass index – from the position of assessment of the condition of patients with ischemic heart disease - G. A. Nagaeva; M. Zh. Zhuraliev; N. P. Yuldoshev; V. N. Li; K. A. Olimov (Евразийский Кардиологический Журнал)
Purpose: comparative analysis of clinical, laboratory and angiographic parameters in patients with coronary artery disease, depending on the level of body mass index (BMI).Material and Methods: 71 patients with coronary artery disease were examined. All underwent general clinical laboratory functional studies and coronary angiography with stenting of the coronary arteries. Depending on the level of BMI, 2 groups of patients were identified: 1 gr. – 36 patients with BMI < 30 kg/m2 and 2 gr. – 35 patients with BMI ³ 30 kg/m2.Results: an increase in BMI was associated with young age and female sex, but fewer acute forms of coronary artery disease. The level of BMI ³ 30 kg/m2 was characterized by greater comorbidity, with AH being more frequent among comorbidities; diabetes; diseases of the gastroduodenal zone GDZ (p < 0,05); COPD and past history of Covid-19. In addition, among patients with a BMI ³ 30 kg/m2, the incidence of complex ventricular cardiac arrhythmias was 4 times higher than in patients with a BMI < 30 kg/m2. In patients with BMI ³ 30 kg/m2, the average amount of medications taken per day was 0,8 less than in the comparison group. The most frequently taken groups of drugs (in addition to BAB and ASA drugs) among patients in group 2 were: calcium antagonists AK; sartans and hypoglycemic drugs, and among patients of group 1 – ACE inhibitors; statins; thienopyridines and antiarrhythmics. 8,5% of the surveyed were NOT adherent to drug treatment, while among patients in group 1 – 13,9% and in group 2 – 2,8% of respondents. An increase in BMI according to ECG data was characterized by an increase in heart rate and a greater predisposition to ventricular arrhythmia, and according to echocardiography, by a thickening of the LV walls and a decrease in its systolic function. Angiographically, higher BMI values were not a criterion for the complexity of vascular lesions. Nevertheless, the length of the atherosclerotic lesion in the respondents in group 2 was greater than in group 1 (p > 0,05). In patients with BMI ³ 30 kg/m2, lesions of the distal segments of the main coronary arteries were recorded comparatively more often, with type B stenosis prevailing in the PNA basin (60,0%); in the RCA basin – type A (31,6%) and type B (47,4%) stenoses.Conclusion: there are still many controversial points in the assessment of the relationship between excess weight and cardiovascular pathology. Nevertheless, the significance of the BMI indicator has its prerogatives in this direction, especially in primary health care at the first contact with a patient.